Functional linkage of gene fusions to cancer cell fitness assessed by pharmacological and CRISPR-Cas9 screening - Picco, Gabriele; Chen, Elisabeth D.; Sáez Rodríguez, Julio (Nature Communications, 2019)
Gene fusions are observed in many cancers but their link to tumour fitness is largely unknown. Here, transcriptomic analysis combined with pharmacological and CRISPR-Cas9 screening of cancer cell lines was used to evaluate the functional linkage between fusions and tumour fitness.
Gabriele Picco and Elisabeth D. Chen contributed equally
Gesehen am 26.06.2019